Association between infection with H. pylori and atopy in young Ethiopian children: a longitudinal study - Taye, Bineyam; Enquselassie, Fikre; Tsegaye, Aster; Amberbir, Alemayehu; Medhin, Girmay; Fogarty, Andrew W.; Robinson, Karen; Davey, Gail (Wiley, 2017)
Background: Epidemiological evidence from developed countries indicates that Helicobacter pylori infection correlates with a reduced risk of atopy and allergic disorders, however limited data are available from low-income countries.